Quantitative metabolomics of the thermophilic methylotroph Bacillus methanolicus. Issue 1 (December 2016) - Carnicer, Marc; Vieira, Gilles; Brautaset, Trygve; Portais, Jean-Charles; Heux, Stephanie
Abstract Background The gram-positive bacteriumBacillus methanolicus MGA3 is a promising candidate for methanol-based biotechnologies. Accurate determination of intracellular metabolites is crucial for engineering this bacteria into an efficient microbial cell factory. Due to the diversity of chemical and cell properties, an experimental protocol validated onB. methanolicus is needed. Here a systematic evaluation of different techniques for establishing a reliable basis for metabolome investigations is presented. Results Metabolome analysis was focused on metabolites closely linked withB. methanolicus central methanol metabolism. As an alternative to cold solvent based procedures, a solvent-free quenching strategy using stainless steel beads cooled to −20 °C was assessed. The precision, the consistency of the measurements, and the extent of metabolite leakage from quenched cells were evaluated in procedures with and without cell separation. The most accurate and reliable performance was provided by the method without cell separation, as significant metabolite leakage occurred in the procedures based on fast filtration. As a biological test case, the best protocol was used to assess the metabolome ofB. methanolicus grown in chemostat on methanol at two different growth rates and its validity was demonstrated. Conclusion The presented protocol is a first and helpful step towards developing reliable metabolomics data for thermophilic methylotrophB. methanolicus. This will definitely help for designing an efficient methylotrophic cell factory.